An Abnormally High Neutrophil-to-Lymphocyte Ratio Is Not an Independent Outcome Predictor in AQP4-IgG-Positive NMOSD - Carnero Contentti, Edgar; Delgado-García, Guillermo; Criniti, Juan; López, Pablo A.; Pettinicchi, Juan Pablo; Cristiano, Edgardo; Miguez, Jimena; Correa-Díaz, Edgar Patricio; Álvarez Pucha, Marcelo Oswaldo; Miño Zambrano, Joselyn Elizabeth; Gómez-Figueroa, Enrique; Rivas-Alonso, Verónica; et al. (Frontiers in Immunology, 2021)
Background: The neutrophil-to-lymphocyte ratio (NLR) has been investigated in many autoimmune conditions as a biomarker of inflammation and/or disease activity. The role of NLR in AQP4-IgG-positive neuromyelitis optica spectrum disorders (NMOSD) is far from clear. In this study, NLR was evaluated in patients with AQP4-IgG-positive NMOSD at disease onset and its prognostic impact was subsequently assessed. Methods: In this multicenter study, we retrospectively included all recent/newly diagnosed treatment-naïve patients with AQP4-IgG-positive NMOSD (n=90) from three different countries in Latin America (LATAM): Argentina, Ecuador, and Mexico. NLR was compared between AQP4-IgG-positive NMOSD and healthy controls (HC, n=365). Demographic, clinical, paraclinical (including imaging), and prognostic data at 12 and 24 months were also evaluated. Multivariate regression analysis was used to describe and identify independent associations between the log-transformed NLR and clinical (relapses and EDSS) and imaging (new/enlarging and/or contrast-enhancing MRI lesions) outcomes. Results: NLR was higher in NMOSD patients during the first attack compared with HC (2.9±1.6 vs 1.8±0.6; p<0.0001). Regardless of immunosuppressant’s initiation at disease onset, NLR remained higher in NMOSD patients at 12 (2.8±1.3; p<0.0001) and 24 (3.1±1.6; p<0.0001) months. No association was found at 12 and 24 months between the log-transformed NLR and the presence of relapses, new/enlarging and/or contrast-enhancing MRI lesions, and/or physical disability. Conclusions: In this cohort of LATAM patients with AQP4-IgG-positive NMOSD, NLR was abnormally high in attacks but also during follow-up. However, a high NLR was not an independent predictor of clinical or imaging outcomes in our models.